Ricardo Doménech, El teatro del exilio, ed. de Fernando Doménech Rico, Madrid, Ediciones Cátedra, 2013, 315 pp. - Fernández Insuela, Antonio (Pygmalion. Revista de teatro general y comparado, 2025)
Ricardo Doménech, El teatro del exilio, ed. de Fernando Doménech Rico, Madrid, Ediciones Cátedra, 2013, 315 pp.